2016
DOI: 10.1142/s0217751x16500597
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on the U(1)L gauge boson in a wide mass range

Abstract: There is a growing interest for the search of new light gauge bosons. The small mass of a new boson can turn various kinds of low-energy experiments to a new discovery machine, depending on their couplings to the standard model particles. It is important to understand the properties of each type of gauge boson and their current constraints for a given mass. While the dark photon (which couples to the electric charges) and the U (1)B−L gauge boson have been well studied in an extensive mass range, the U (1)L ga… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 83 publications
0
20
0
Order By: Relevance
“…However, if SM fields are charged in a vectorlike fashion, for instance differences of baryon/lepton number between two generations, then no additional fermions are necessary. We expect that DUNE will have the strongest sensitivity to such new physics when the new symmetry is leptophilic, and therefore focus on the case of a L α − L β gauge boson with α, β = e, µ, τ [75][76][77][78][79][80][81][82][83][84][85][86][87][88].…”
Section: Section 5: Leptophilic Gauge Bosonsmentioning
confidence: 99%
“…However, if SM fields are charged in a vectorlike fashion, for instance differences of baryon/lepton number between two generations, then no additional fermions are necessary. We expect that DUNE will have the strongest sensitivity to such new physics when the new symmetry is leptophilic, and therefore focus on the case of a L α − L β gauge boson with α, β = e, µ, τ [75][76][77][78][79][80][81][82][83][84][85][86][87][88].…”
Section: Section 5: Leptophilic Gauge Bosonsmentioning
confidence: 99%
“…9 This result corrects the conclusion of [14], where a simplified estimate suggested that the measured π 0 branching ratio was inconsistent with measurements of η → µ + µ − for the same A mass and axial couplings. 10 The neutrino-electron bounds here are translated from [31] by assuming c e A ∼ c e V , c νµ ∼ κc νe , which is true for a generic point in the 2HDM parameter space and suffices to illustrate the dominance of neutrino bounds for large κ. Figure 4.…”
Section: Surveying the Parameter Spacementioning
confidence: 99%
“…LEP experiments. The high mass regions are sensitive to the LEP experiments which give the exclusion limit depicted by the brown region [56]. The constraint for the contact interactions [57] is valid only for the M Z much larger than the collision energy at LEP, 209 GeV, while the initial state photon radiation process, e + e − → γνν [58], can be used for the M Z lower than the collision energy.…”
Section: Jhep02(2017)031mentioning
confidence: 99%